2014
DOI: 10.1096/fj.13-244004
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin‐3 enhances breast cancer progression and metastasis by activating Twist‐mediated angiogenesis

Abstract: The FERM domain containing protein Kindlin-3 has been recognized as a major regulator of integrin function in hematopoietic cells, but its role in neoplasia is totally unknown. We have examined the relationship between Kindlin-3 and breast cancer in mouse models and human tissues. Human breast tumors showed a ∼7-fold elevation in Kindlin-3 mRNA compared with nonneoplastic tissue by quantitative polymerase chain reaction. Kindlin-3 overexpression in a breast cancer cell line increased primary tumor growth and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
87
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 39 publications
6
87
2
Order By: Relevance
“…Kindlin-3 is expressed primarily in white blood cells; its loss of function is associated with leukocyte attachment deficiency (LAD) (38). Overexpression of Kindlins has been detected frequently in human cancers (39)(40)(41). We focused on the function of kindlin-2 in fibroblasts, as they control the production of many extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Kindlin-3 is expressed primarily in white blood cells; its loss of function is associated with leukocyte attachment deficiency (LAD) (38). Overexpression of Kindlins has been detected frequently in human cancers (39)(40)(41). We focused on the function of kindlin-2 in fibroblasts, as they control the production of many extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the human and mouse genomes revealed the existence of three Mig-2/kindlin isoforms (Siegel et al, 2003), and expression analyses revealed that the three Mig-2/kindlin family members are expressed in different cells and tissues (Ussar et al, 2006). Kindlin-1 is mainly expressed in epithelial cells, kindlin-2 is broadly expressed but absent in all blood cells analyzed so far (Ussar et al, 2006), and kindlin-3 is found in hematopoietic cells and, possibly, also at low levels in endothelial cells and in solid cancers, such as breast cancer and melanoma (Sossey-Alaoui et al, 2014;Djaafri et al, 2014;Delyon et al, 2015). It is unclear whether the expression of kindlin-3 in solid tumors is caused by de novo activation of the KINDLIN-3 gene or by infiltration of hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Kindlin-3 mutations in have been identified in humans with a rare syndrome referred to as LADIII (21)(22)(23)(24)(25) with manifestations that include episodic bleeding, susceptibility to frequent infections and osteopetrosis, which are consequences of an inability to activate ␤ 1 , ␤ 2 and ␤ 3 integrin (22,23,25), and variably in abnormal red cell shapes (25). Kindlin-3 is also present and functional in endothelial cells (26) and breast cancer cells (27), where it acts as a tumor promoter (27). Despite this ample evidence emphasizing the role of kindlin-3 in integrin function in variety of cells, the mechanisms underlying kindlin-mediated integrin activation are largely unknown.…”
mentioning
confidence: 99%